MUSCLE AND BRAIN ACTIVITY OF A PERSON UNDER THE INFLUENCE OF DIETARY SUPPLEMENTS - Омонова Севара Акрамжоновна; Нишоновa Севинч Олимжон кизи (Modern American Journals, 2025)
Modern living conditions are characterized by a high level of physical and psycho-emotional stress, insufficient intake of nutrients and low motor activity, which leads to a decrease in energy metabolism, weakening of muscle tone and cognitive functions. In this regard, of particular interest is the use of dietary supplements (BAA) containing proteins, amino acids, creatine, omega-3 fatty acids, vitamins and trace elements, which play a key role in the regulation of metabolism, energy balance and neural activity. Their study is important both for sports medicine and for the prevention of age-related changes in muscle and brain activity.